2018
DOI: 10.1371/journal.pone.0195751
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody targeting amyloid β (Aβ) restores complement factor I bioactivity: Potential implications in age-related macular degeneration and Alzheimer’s disease

Abstract: Activation of the alternative complement cascade has been implicated in the pathogenesis of age related macular degeneration (AMD) and Alzheimer’s disease (AD). Amyloid β (Aβ), a component of drusen, may promote complement activation by inhibiting CFI bioactivity. We determined whether Aβ reduced CFI bioactivity and whether antibodies against Aβ including a monoclonal antibody, GSK933776 could restore CFI bioactivity. We also measured CFI bioactivity in plasma of subjects with AMD and AD. In support of the GSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Aged CXCR5 −/− mice present retinal degeneration, with photoreceptor cell death, upregulation of TNF and breakdown of the outer blood-retinal barrier. Moreover, these animals exhibit drusen-like deposits and the presence of Aβ and Cryab, two abundant proteins that are present in Bruch's membrane and choroidal tissues of AMD patients [167,168]. Aβ and Cryab induce activation of the alternative complement cascade and are a target for microglia adaptive immune responses [167,169].…”
Section: The Contribution Of Microglia To Retinal and Choroidal Neovamentioning
confidence: 99%
“…Aged CXCR5 −/− mice present retinal degeneration, with photoreceptor cell death, upregulation of TNF and breakdown of the outer blood-retinal barrier. Moreover, these animals exhibit drusen-like deposits and the presence of Aβ and Cryab, two abundant proteins that are present in Bruch's membrane and choroidal tissues of AMD patients [167,168]. Aβ and Cryab induce activation of the alternative complement cascade and are a target for microglia adaptive immune responses [167,169].…”
Section: The Contribution Of Microglia To Retinal and Choroidal Neovamentioning
confidence: 99%
“…As we all known, Aβ is one important pathological characteristic of AD [27], which may induce the activation of the classical complement pathway in AD brains [28,29]. Moreover, CR1 is a necessary component of complement system, and it has been reported to have a close connection with amyloid plaque burden during aging [30,31].…”
Section: Discussionmentioning
confidence: 98%
“…Aβ may also induce toxicity at the PR level by impacting their ribosomal machinery and oxidative phosphorylation by increasing phosphorylation of tau protein and dysregulating glycogen synthase kinase-3 beta (GSK3β) [29]. We have recently shown that Aβ can inhibit the activity of CFI, one of the key breaks in the alternative complement pathway leading to a shift in overproduction of C3b (active pathway) in lieu of production of iC3b which as a consequence inactivates the pathway [30]. Increased C3b leads to the eventual production of C5b678(9) membrane attack complex via the alternative complement pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Increased C3b leads to the eventual production of C5b678(9) membrane attack complex via the alternative complement pathway. However, a clinical study attempting to block the action of Aβ via systemic administration of an anti-Aβ antibody (GSK933776) failed to reduce GA progression rate [31], probably because of the inability of systemic administration to achieve sufficiently high concentrations of the antibody at the level of the RPE/Bruch's membrane interphase [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation